2018
DOI: 10.1111/joa.12776
|View full text |Cite
|
Sign up to set email alerts
|

Systemic patterns of trabecular bone across the human and chimpanzee skeleton

Abstract: Aspects of trabecular bone architecture are thought to reflect regional loading of the skeleton, and thus differ between primate taxa with different locomotor and postural modes. However, there are several systemic factors that affect bone structure that could contribute to, or be the primary factor determining, interspecific differences in bone structure. These systemic factors include differences in genetic regulation, sensitivity to loading, hormone levels, diet, and activity levels. Improved understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 127 publications
(406 reference statements)
4
79
1
Order By: Relevance
“…PREPRINT discriminating parameter in extant xenarthrans (Amson et al 2017a). It was also singled out as reflecting joint loading in primates better than other parameters (Tsegai et al 2018), and, more generally, DA was found as functionally informative in several analyses about that clade (e.g. Ryan & Ketcham 2002;Griffin et al 2010;Barak et al 2013;Su et al 2013;Georgiou et al 2018;Ryan et al 2018;Tsegai et al 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…PREPRINT discriminating parameter in extant xenarthrans (Amson et al 2017a). It was also singled out as reflecting joint loading in primates better than other parameters (Tsegai et al 2018), and, more generally, DA was found as functionally informative in several analyses about that clade (e.g. Ryan & Ketcham 2002;Griffin et al 2010;Barak et al 2013;Su et al 2013;Georgiou et al 2018;Ryan et al 2018;Tsegai et al 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Comparative studies focusing on either trabeculae or cortical structure intend to leverage this great plasticity to associate structural phenotypes to PREPRINT lifestyles or functional uses of a limb. This has been achieved in some analyses (as recently exemplified by Georgiou et al 2018;Ryan et al 2018;Tsegai et al 2018) but not all of them (see review of Kivell 2016), suggesting that some confounding factors are likely to be at play, and more generally that the approach is limited. For trabecular bone in particular, important intraspecific variation has been documented (e.g., in Pongo; Tsegai et al 2013;Georgiou et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While these results appear consistent with what is known of hominid behavior and anatomy, the function of trabecular bone is not only biomechanical but also physiological, as it is important for mineral homeostasis (Clarke, ). Furthermore, trabecular structure may be affected by systemic factors, including the gut biomes of an animal (Tsegai et al, ) and is determined genetically to some extent (Almécija, Wallace, Judex, Alba, & Moyà‐Solà, ; Havill et al, ; Judex, Zhang, Donahue, & Ozcivici, ; Lovejoy et al, ). Some researchers have also argued that functional adaptation of bone is largely limited to mechanical strains experienced during growth (Bertram & Swartz, ; Lovejoy et al, ; Wallace et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This standardization of BV/TV values was performed for several reasons. BV/TV can vary systemically across species (Tsegai, Skinner, Pahr, Hublin, & Kivell, ) and thus may diminish the potential functional signal under investigation here. Further, while BV/TV yields functional information relating to the response of trabecular bone to both magnitude and direction of load, it conflates these signals.…”
Section: Methodsmentioning
confidence: 99%
“…However, hand‐in‐hand with the increase in publications relating to bone functional adaptation, which is a bone modeling mechanism, the important distinction between bone modeling and bone remodeling was repeatedly dismissed as a mere terminology issue. This led some authors to address all adjustments of bone morphology related to loading, especially in the case of trabecular bone, as bone remodeling (Dunmore, Kivell, Bardo, & Skinner, ; Hoechel, Schulz, & Müller‐Gerbl, ; Kivell, ; Kivell, Davenport, Hublin, Thackeray, & Skinner, ; Saers, Ryan, & Stock, ; Tsegai, Skinner, Pahr, Hublin, & Kivell, , ; Zeininger, Richmond, & Hartman, ). The aim of this commentary is to elucidate the key differences between bone modeling and bone remodeling and to stress the importance of using the correct term, that is, bone modeling, when referring to trabecular bone structural adaptation in response to loading.…”
mentioning
confidence: 99%